Gold Price Dynamics and Earnings Performance in a Non-Bank Gold-Backed Finance Firm - Sitti Hajerah Hasyim; Fajriani Azis; Salim Diarra (Global Research Collaboration, 2025)
This study examines whether benchmark gold prices affect profit achievement in a state-owned pawn and gold-financing company. Using branch-level financial statements for 2020–2024, we estimate a single-factor ordinary least squares model to test the association between gold price movements and profitability. The results show a positive and statistically significant relationship, indicating that higher gold prices are associated with improved profits—consistent with collateral value uplift, trading spreads, and product demand dynamics in gold-backed lending. Managerially, the findings suggest the need for agile pricing policies, transparent customer communication on gold price pass-through, and strengthened risk management to handle volatility. The study contributes firm-level evidence on price–profit linkages in gold-backed retail finance. Limitations include a single-firm, single-factor design; future research should incorporate cost structures, fee income, macroeconomic controls, and asymmetric/lagged effects to better map the transmission from commodity prices to financial performance.